Strategic management accounting in small and medium-sized enterprises in emerging countries and markets: A case study from China - Lindong Ma; Xihui Chen; Jiawen Zhou; Luigi Aldieri (Economies, 2022)
Small and medium-sized enterprises (SMEs) play an increasingly important role in global economic development, and they have encountered many unique problems (such as resources and strategic choice). Strategic management accounting (SMA) techniques can help SMEs allocate limited resources rationally and integrate internal and external information to help managers make strategic decisions. However, how and what is the SMA applied in the reality of SMEs, especially in developing countries today. This paper aims to explore the extent to which SMEs of developing countries use SMA. This article used the qualitative research method and the data were collected by interviewing five managers and two employees in M company. The findings indicated that: (1) The senior managers of SMEs do not have an understanding of accounting nor pay enough attention to it, and the role of SMA is even worse; (2) Although the chief financial officers obtain the knowledge of SMA, they cannot fully involve it in their strategic decision making. (3) SMEs have realized that enterprise culture is very important for a company to achieve strategic goals, but it is far from enough to attach importance to and create it. (4) The general managers of SMEs believe that the operating department is the core of the company and all resources should be prioritized to meet their needs.
Keywords: 330; case study; China; small and medium-sized enterprises (SMEs); strategic management accounting (SMA)